Subacute Right Ventricle Perforation by Pacemaker Lead Presenting with Left Hemothorax and Shock - Julianne Nichols; Natalie Berger; Praveen Joseph; Debapriya Datta (Case Reports in Cardiology)
Cardiac perforation by pacemaker is a rare but potentially fatal complication. Acute perforations occurring within twenty-four hours of insertion of pacemaker can lead to hemopericardium, cardiac tamponade, and death. Hemothorax occurring as an acute complication of pacemaker insertion is reported but extremely rare. Previously, hemothorax and shock as a subacute complication following pacemaker insertion have not been reported. We report the case of an 85-year-old patient who presented with shock from hemothorax caused by pacemaker perforation, two weeks after insertion. Device interrogation showed normal function. Chest X-ray and echocardiogram missed lead dislocation and the diagnosis was made on computed tomogram (CT) of the chest. Following surgical repair, a new ventricular pacemaker was placed transvenously in the right ventricular septum. This case illustrates that CT scan of the chest should be performed in all patients in whom cardiac perforation by pacemaker is suspected but not diagnosed on chest X-ray and echocardiogram. Normal functioning of pacemaker on device interrogation does not exclude perforation.